2018
DOI: 10.1080/21645515.2018.1496766
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory and recommended vaccinations in Poland in the views of parents

Abstract: Background: Vaccinations are currently the key element in the prevention of the spread of infectious diseases. We studied parents' opinions about mandatory and recommended preventive vaccinations in Poland. Methods: A diagnostic survey using an original questionnaire was done in a group of 300 parents. Results: A total of 3.7% of parents did not vaccinate their children. 90% were aware of the threat potentially posed by infectious diseases, and 73.7% knew that breastfeeding alone does not ensure sufficient pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
(28 reference statements)
1
20
0
1
Order By: Relevance
“…The scope of com-pulsory vaccinations differs between European countries. Some countries, including Poland, have a legally regulated program of mandatory vaccinations in place [1][2][3]. In Poland, mandatory vaccinations are regulated by the Act of December 5, 2008 on the Prevention and Control of Infections and Infectious Diseases in Humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of com-pulsory vaccinations differs between European countries. Some countries, including Poland, have a legally regulated program of mandatory vaccinations in place [1][2][3]. In Poland, mandatory vaccinations are regulated by the Act of December 5, 2008 on the Prevention and Control of Infections and Infectious Diseases in Humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…Five quantitative studies scored particularly poorly (between three and five). [36-41] These studies were poor across the different dimensions evaluated, but low scores were because participants were not representative of the target population, complete outcome data were not reported, confounders were not accounted for in the study design and analysis, and outcome variables were not robustly measured.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found no evidence for an association between parent gender and support for mandatory vaccination schemes. [29, 30, 35-37] One poor quality study found an association between younger age and lower support for mandatory vaccination,[36, 37] while three studies (two good quality, one moderate quality) found no evidence for an association. [29, 30, 35] A further poor quality study found that parents of younger children were less likely to support mandatory vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations